Reliability, risk and safety : theory and applications : proceedings of the European Safety and Reliability Conference, ESREL 2009, Prague, Czech Republic, 7-10 September 2009 /: theory and applications : proceedings of the European Safety and Reliability Conference, ESREL 2009, Prague, Czech Republic, 7-10 September 2009. (©2010) - Unknown
No abstract available